2016
DOI: 10.1021/acs.organomet.5b00937
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of N-Heterocyclic PSiP Pincer Iron and Cobalt Complexes and Catalytic Application of Cobalt Hydride in Kumada Coupling Reactions

Abstract: The new N-heterocyclic σ-silyl pincer ligand HSiMe­(NCH2PPh2)2C6H4 (1) was designed. A series of tridentate silyl pincer Fe and Co complexes were prepared. Most of them were formed by chelate-assisted Si–H activation. The typical iron hydrido complex FeH­(PMe3)2(SiMe­(NCH2PPh2)2C6H4) (2) was obtained by Si–H activation of compound 1 with Fe­(PMe3)4. The combination of compound 1 with CoMe­(PMe3)4 afforded the Co­(I) complex Co­(PMe3)2(SiMe­(NCH2PPh2)2C6H4) (3). The Co­(III) complex CoHCl­(PMe3)­(SiMe­(NCH2PPh2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 34 publications
0
27
0
1
Order By: Relevance
“…Intramolecular cyclization and subsequent aromatization of α,α‐dicyanoolefin‐comprising motifs towards polysubstituted m ‐terphenyls in the presence of a base was reported by Xue, Deng, and co‐authors . Instead, for synthesis of sterically more demanding o ‐terphenyls, classical synthetic approaches, for example, Kumada coupling or Suzuki coupling, are commonly employed. Substituted o ‐terphenyls are important intermediate compounds for the synthesis of polyaromatic hydrocarbons (PAHs) for the fabrication of organic light‐emitting diodes (OLEDs), and are subunits of synthetic anti‐inflammatory and anticoagulant pharmaceuticals .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intramolecular cyclization and subsequent aromatization of α,α‐dicyanoolefin‐comprising motifs towards polysubstituted m ‐terphenyls in the presence of a base was reported by Xue, Deng, and co‐authors . Instead, for synthesis of sterically more demanding o ‐terphenyls, classical synthetic approaches, for example, Kumada coupling or Suzuki coupling, are commonly employed. Substituted o ‐terphenyls are important intermediate compounds for the synthesis of polyaromatic hydrocarbons (PAHs) for the fabrication of organic light‐emitting diodes (OLEDs), and are subunits of synthetic anti‐inflammatory and anticoagulant pharmaceuticals .…”
Section: Resultsmentioning
confidence: 99%
“…Instead, for synthesis of sterically more demanding o ‐terphenyls, classical synthetic approaches, for example, Kumada coupling or Suzuki coupling, are commonly employed. Substituted o ‐terphenyls are important intermediate compounds for the synthesis of polyaromatic hydrocarbons (PAHs) for the fabrication of organic light‐emitting diodes (OLEDs), and are subunits of synthetic anti‐inflammatory and anticoagulant pharmaceuticals . Therefore, the development of new convenient and sustainable synthetic methods towards o ‐terphenyls is highly desirable.…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicate that the synthesiso f5 as ac helate complex is easier than that of our [PSiP]-pincer cobalt hydride. [11] With similarc atalytic efficiency for Kumada reactions, the catalytic loading (2 %) of 5 is lower than that (5 %) of [PSiP]-pincer cobalt hydride.…”
Section: Introductionmentioning
confidence: 93%
“…We reported that a[ PSiP]-pincer silyl hydrido cobalt chloride could catalyze Kumadacoupling reactions. [11] Complex 5 is ahydrido silyl [P,Si]-chelate Co III chloride with aC o ÀHa nd aC o ÀCl bond.T his structure was assumedt ob eu nstable under certain conditions, andc ould be ap otential catalyst. Encouraged by these results, as eries of Kumada coupling reactionsc atalyzed by complex 5 were studied.…”
Section: Catalytic Application Of Silyl Hydrido Complex 5ink Umada Comentioning
confidence: 99%
See 1 more Smart Citation